Evaluation of the protective effect of Myrtus communis in scopolamine induced Alzheimer model through cholinergic receptors - ŞEN, ALİ; ERTAŞ, BÜŞRA; ÖZBEYLİ, DİLEK; ŞENER, GÖKSEL; KILINÇ, OLCA; ORUN, OYA (ELSEVIER, 2019)
Alzheimer's disease is a progressive neurodegenerative disorder causing common health problem with increasing age. Evidences show that the key symptoms of AD are mainly caused by cholinergic system dysfunction which has a role in cognitive disorders. Cholinergic pathways especially muscarinic receptors like M-1 subtype also have a major role in learning, memory, cognitive functions and emotional state. There is no available permanent treatment currently to cure AD or to change its progression. This study was designed to investigate the factors that play important role in pathogenesis of AD and to compare the effects of Galantamine treatment with effects of Myrtus communis treatment. The expression level of M-1, ACh, BDNF; AChE activity, GSH level, MDA and MPO activity and AChE gene expression were investigated in scopolamine-induced rat model. Results showed that, administration of MC significantly improves the SCOP-induced reduction of latency and object recognition time; increasing BDNF, M-1 and ACh receptor expression levels in the different brain regions. Additionally, MC showed an increased in AChE by enhancing GSH activity and reducing MDA level and MPO activity. In conclusion MC considered as a possible novel therapeutic approach that can be a valuable alternative way in the prevention and treatment of AD.
Keywords: Myrtus communis; Scopolamine; Muscarinic reseptor M-1; BDNF; AChE; INDUCED MEMORY IMPAIRMENT; OXIDATIVE STRESS; ACETYLCHOLINESTERASE INHIBITION; RATS; NEUROINFLAMMATION; DISEASE; BRAIN; L.; INFLAMMATION; RECOGNITION